Studi Perladangan Berpindah Dari Suku Wemale Di Kecamatan Inamosol Kabupaten Seram Bagian Barat - Johan M Matinahoru (Agrologia, 2013)
Shifting cultivation is a farming system  in which farmers  cultivate through a movement of activity from a place to another  in the secondary or primary forest. Wemale tribe in the Inamosol District of West Seram Regency are able to open forest area about 0.2 – 1.0 hectare in each year for practing the shifting cultivation. To understand how Wemale tribe practiced the shifting cultivation, a research has been  conducted with the main objevtive to know the factors that determined  the variation of the land size of the shifting cultivation. The method used in the research was by interview and direct observation in the field. The results of the research indicated that variation of land size of the shifting culvation that was practiced by the Wemale tribe were the number of  household labors and the number  of children in the household that were still active in the process of education